Articular cartilage chondrocytes express aromatase and use enzymes involved in estrogen metabolism - Schicht, Martin; Ernst, Jana; Nielitz, Andrea; Fester, Lars; Tsokos, Michael; Guddat, Saskia S.; Bräuer, Lars; Bechmann, Judith; Delank, Karl-Stefan; Wohlrab, David; Paulsen, Friedrich; Claassen, Horst (Arthritis Research & Therapy, 2014)
Sex hormones, especially estrogens, have been implicated in articular cartilage metabolism and the pathogenesis of postmenopausal osteoarthritis. The conversion by aromatase (CYP19A1) of androstenedione into estrone (E1) and of testosterone into 17?-estradiol (E2) plays a key role in the endogenous synthesis of estrogens in tissue.We analyzed the expression of aromatase (CYP19A1) in immortalized C-28/I2 and T/C-28a2 chondrocytes, as well as in cultured primary human articular chondrocytes and human articular cartilage tissue, by means of RT-PCR, Western blotting and immunohistochemistry. By means of quantitative RT-PCR and enzyme-linked immunosorbent assay, we also determined whether the aromatase inhibitor letrozole influences estrogen metabolism of cultured chondrocytes in immortalized C-28/I2 chondrocytes.Aromatase mRNA was detected in both immortalized chondrocyte cell lines, in cultured primary human chondrocytes, and in human articular cartilage tissue. By means of Western blot analysis, aromatase was detected at the protein level in articular cartilage taken from various patients of both sexes and different ages. Cultured primary human articular chondrocytes, C-28/I2 and T/C-28a2, and human articular cartilage tissue reacted with antibodies for aromatase. Incubation of C-28/I2 chondrocytes with 10?¹¹ M to 10??M letrozole as an aromatase inhibitor revealed significantly increased amounts of the mRNAs of the enzyme cytochrome P4501A1 (CYP1A1), which is involved in the catagen estrogen metabolism, and of the estrogen receptors ER-? and ER-?. Concomitantly, synthesis of estrone (E1) was significantly downregulated after incubation with letrozole.We demonstrate that human articular cartilage expresses aromatase at the mRNA and protein levels. Blocking of estrone synthesis by the aromatase inhibitor letrozole is counteracted by an increase in ER-? and ER-?. In addition, CYP1A1, an enzyme involved in catabolic estrogen metabolism, is upregulated. This suggests that articular chondrocytes use ERs functionally. The role of endogenous synthesized estrogens in articular cartilage health remains to be elucidated.
EVALuna2:4411